A multiprotein regulatory module, MED16–MBR1&2, controls MED25 homeostasis during jasmonate signaling - Fangming Wu; Chuanlong Sun; Ziying Zhu; Lei Deng; Feifei Yu; Qi Xie; Chuanyou Li (Nature Communications)
Abstract Mediator25 (MED25) has been ascribed as a signal-processing and -integrating center that controls jasmonate (JA)-induced and MYC2-dependent transcriptional output. A better understanding of the regulation of MED25 stability will undoubtedly advance our knowledge of the precise regulation of JA signaling-related transcriptional output. Here, we report that Arabidopsis MED16 activates JA-responsive gene expression by promoting MED25 stability. Conversely, two homologous E3 ubiquitin ligases, MED25-BINDING RING-H2 PROTEIN1 (MBR1) and MBR2, negatively regulate JA-responsive gene expression by promoting MED25 degradation. MED16 competes with MBR1&2 to bind to the von Willebrand Factor A (vWF-A) domain of MED25, thereby antagonizing the MBR1&2-mediated degradation of MED25 in vivo. In addition, we show that MED16 promotes hormone-induced interactions between MYC2 and MED25, leading to the activation of JA-responsive gene expression. Collectively, our findings reveal a multiprotein regulatory module that robustly and tightly maintains MED25 homeostasis, which determines the strength of the transcriptional output of JA signaling.